Public, privé,... ou hybride ? - Annie Vinokur (Les éditions de la Maison des sciences de l'Homme, 2004)
Is education a public or a private good? Should it be provided by the State or the market? These long-standing debates are now blurred by the fact that the frontiers between what is public and what is private in education are rapidly fading. What is emerging is a generalised process of hybridisation. The aim of this paper is to assess some empirical aspects of this movement, to analyse its legitimisation in the "good governance" doctrine, and to question what is at stake in this critical transformation of our education systems.